Short course of ofloxacin for treatment of multidrug-resistant typhoid - Tran Tinh Hien (2018)
In recent years, multiresistant strains of Salmonella typhi have emerged in many tropical countries. These strains remain highly sensitive to the fluoroquinolone antibiotics, although use of these drugs by children is considered contraindicated because of their reported toxicity in the cartilage of experimental animals. In a paired, open, randomized study during an epidemic of multidrug-resistant typhoid in southern Vietnam, two short-course ofloxacin regimens (15 mg/kg daily for 3 days and 10 mg/kg daily for 5 days) were compared for the treatment of uncomplicated typhoid fever. Of 438 patients enrolled (of whom 286 were ≤14 years old), 228 had blood cultures positive for Salmonella species (S. typhi, 207; S. paratyphi A, 19; and S. choleraesuis, 2). There was one treatment failure in a patient who took only one dose of ofloxacin. Otherwise, both regimens were completely effective; there were no proven carriers, and there was no evidence of toxicity, particularly in children. A 3-day course of ofloxacin proved to be safe and highly effective in the treatment of uncomplicated, multidrug-resistant typhoid fever. © 1995 by The University of Chicago. All rights reserved.